Theoretical and Methodological Aspects of Shaping Social Behavior in Higher School - A. V. Korotkov (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
The goal of the research is to attract attention to the problem of upbringing and to the necessity of improving theoretical and methodological support of the process of social upbringing of students in higher school oriented to shaping social behavior of students directly in the education institution that corresponds to the cultural level, standards and rules of this education institution. Legislative acts and academic publications concerning learners’ upbringing were used as sources of information. Certain categories and notions used in researching social upbringing and behavior have not been completely shaped, thus the present investigation was based on scientific methodology, which includes as one of its sections improvement and concretization of conceptual and categorical apparatus in this field of science. During the research in order to describe the process of shaping social behavior in higher school the authors used systematic, cybernetic approach implying modeling of the upbringing process in the form of model of managing the process of learner’s socialization assuming demand setting, monitoring results and correction of management by feedback. The research used elements of planning with development of the list of tasks and events aimed at managing the process of social behavior of student. As a result the conceptual and categorical apparatus was specified and formulated, which is necessary to describe the process of student’s socialization in education institutions, including such notions as social upbringing, socialization, social behavior, organizational behavior, behavior discipline, behavior code, behavior culture, organizational discipline; the model of managing the process of shaping social behavior of student was worked out in the form of the system with feedback; the list of tasks and events was developed to support the process of managing social behavior with assessment of their applicability in current situation. The obtained results can form the foundation for developing the mechanism of managing social behavior in university and can be used not only in higher school but also in other education institutions.